Comparison of albumin-bilirubin grade, platelet-albumin-bilirubin grade and Child-Turcotte-Pugh class for prediction of survival in patients with large hepatocellular carcinoma after transarterial chemoembolization combined with microwave ablation. (1st January 2019) - Ni, Jia-Yan; Fang, Zhu-Ting; An, Chao; Sun, Hong-Liang; Huang, Zhi-Mei; Zhang, Tian-Qi; Jiang, Xiong-Ying; Chen, Yao-Ting; Xu, Lin-Feng; Huang, Jin-Hua
Abstract: Purpose: To compare the predictive value of albumin-bilirubin (ALBI) grade, platelet-ALBI (PALBI) grade and Child-Turcotte-Pugh (CTP) class in patients with large hepatocellular carcinoma (HCC) after transarterial chemoembolization (TACE) combined with microwave ablation (TACE-MWA). Methods: A total of 349 consecutive HCC patients (89.1% male; mean [± SD] age 53.4 ± 12.27 years) from three medical centers, who underwent TACE-MWA for up to 3 HCCs with maximum diameters of 5.1–8.0 cm between January 2000 and June 2018, were investigated. Overall survival (OS) and progression-free survival (PFS) were analyzed. The prognostic performances of ALBI grade, PALBI grade and CTP class were compared. Results: TACE procedures were performed using lobaplatin (20–50 mg), epirubicin (30–60 mg), lipiodol (5–25 mL) and gelatin sponge particles (350–560 μm). The end point of the TACE procedure was stasis of blood flow in the feeder artery. The median follow-up duration was 28.0 months, the median OS was 28.0 months (95% confidence interval [CI] 23.55–32.45 months), and the median PFS was 4.8 months (95% CI 4.26–5.34 months). Patients with a ablation margin size of 11–15 mm experienced better PFS than those with a margin size of 6–10 or 0–5 mm (median, 6.5 versus [vs] 4.0 vs 2.3 months; p  < .001). PALBI grade demonstrated significantly greater area under the curve values than ALBI grade or CTP class in predicting 1-, 3- and 5-year OS. Conclusions: PALBI grade provided better predictive value than ALBI grade or CTP class in patients with large HCCs after TACE-MWA.